2010
DOI: 10.1007/s11219-009-9092-9
|View full text |Cite
|
Sign up to set email alerts
|

SPDW+: a seamless approach for capturing quality metrics in software development environments

Abstract: Among the key factors for the success of a metrics program are the regularity of metrics collection, a seamless and efficient data collection methodology, and the presence of non-intrusive automated data collection tools. This paper presents the software process data warehousing architecture SPDW? as a solution to the frequent, seamless, and automated capturing of software quality metrics, and their integration in a central repository for a full range of analyses. The striking features of the SPDW? ETL (data e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Most of the proposals include mechanisms for data analysis and presentation. Some proposals, such as SPDW+ [26] and PAU [28], have more complex mechanisms and tools. The analysis can be purely qualitative, as in WebEv [22,23], or have a benchmark type, as in NSDIR [24] and MRS [25], in which general data of products and projects can be analyzed to support identification of best practices.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the proposals include mechanisms for data analysis and presentation. Some proposals, such as SPDW+ [26] and PAU [28], have more complex mechanisms and tools. The analysis can be purely qualitative, as in WebEv [22,23], or have a benchmark type, as in NSDIR [24] and MRS [25], in which general data of products and projects can be analyzed to support identification of best practices.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we observed that the proposals that include support to statistical process control (SPDW+ [26] e MMR Tool [17]) adopt solutions based on data warehouse.…”
Section: Storagementioning
confidence: 99%
See 3 more Smart Citations